Enzymatic properties, crystallization, and deduced amino acid sequence of an alkaline endoglucanase from Bacillus circulans - Hakamada, Yoshihiro; Endo, Keiji; Takizawa, Shuichi; Kobayashi, Tohru; Shirai, Tsuyoshi; Yamane, Takashi; Ito, Susumu (Biochimica et Biophysica Acta (BBA) - General Subjects, 2002)
A high-isoelectric-point (p I), alkaline endo-1,4-β-glucanase (Egl-257) of Bacillus circulans KSM-N257 was purified to homogeneity and crystallized. The purified enzyme hydrolyzed carboxymethyl cellulose (CMC) with optima of pH 8.5 and 55 °C. The molecular mass was 43 kDa, and the p I was pH 9.3. The structural gene contained a single open reading frame of 1221 bp, corresponding to 407 amino acids (aa), including a 30-aa signal peptide (377 aa and 41,680 Da for the mature enzyme). Egl-257 hydrolyzed lichenan and showed 76.3% aa identity to a lichenase from B. circulans WL-12 belonging to glycosyl hydrolase family 8 but did not hydrolyze laminarin, curdran, and xylan at all. This indicates that Egl-257 is a true endo-1,4-β-glucanase. However, this enzyme was not active on p-nitrophenyl β- d-cellotrioside and p-nitrophenyl β- d-cellotetraoside. It was crystallized by the hanging-drop vapor-diffusion method with phosphate plus CdCl 2 as precipitant. Pyramid-like crystals were formed, and they diffracted X-rays beyond 2.2 Å resolution. It belongs to the space group P2 12 12 1 with unit cell parameters of a=62.5 Å, b=71.7 Å, and c=88.6 Å.